(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The article attempts to reconstruct the concept of war in Polish in accordance with the assumptions of Lublin cognitive ethnolinguistics. The reconstruction is based on dictionary definitions documenting the semantic development of the lexeme war from the 16th century to modern times as well as so-called “linguistic evidence”, in which the most characteristic semantic features of war are entrenched. The article presents the results of conducted surveys. The press material examined in this study encompasses mainly journalistic texts from the online edition of the left-liberal “Krytyka Polityczna” (KP) and the right-wing conservative “Gazeta Polska Codziennie” (GPC). The conducted analysis has led to the conclusion that both dailies expressed content and judgements about the war (in Ukraine) often in different ways. The reference to a different system of values was particularly significant: democratic and liberal (KP) vs. Christian, national and patriotic (GPC)